Hernia and Abdominal Wall Reconstruction for the Colorectal Surgeon - Buxey, Kenneth (Clinics in Colon and Rectal Surgery, 2022)
Hernia remains a challenge for the colorectal surgeon both in regard to prevention of hernia, that is a common entity following colorectal surgery and in managing hernia which is often made more challenging by the co-existence of a significant colorectal-specific problem. This review outlines the extent of hernia as a problem for the colorectal surgeon and highlights contemporary approaches to dealing with patients who require both colorectal and complex hernia surgery.
Keywords: hernia; parastomal; transverus abdominus release; component separation